Reproduction of soil resources in the system of sustainable agricultural land use - Barvinskyi, A.; Loshakova, Y. (Land Management, Cadastre and Land Monitoring, 2020)
The current state of use of soil resources in the agricultural sector of the country is analyzed. It is established that the soil cover, which is the basis of agricultural landscapes, is characterized by high agricultural potential, which allows depending on the climatic conditions of a particular region and genetic characteristics of crops to yield at 30-35 kg / ha of grain units and above. However, due to the significant exceeding of the limit of ecological stability of soils, as evidenced by the practice of agricultural production, various destructive processes are accelerating, which now almost completely covered the lands of the country under intensive cultivation. Particularly vulnerable in this context are the soil resources of Polissya due to the predominantly light particle size distribution and, accordingly, low ability to withstand the negative impact of external factors. It is proved that an effective measure to ensure the preservation and reproduction of soil resources is land management, which ensures the improvement of land relations, planning and organization of rational use and protection of land at all levels from national to economic. In particular, in the Polissya area, this role should be performed by working land management projects to protect lands from acidification, which determine the procedure for chemical reclamation of acid soils in relation to specific socio-economic and environmental conditions of land entities.Key words: agricultural land use, working land management project, soil resources, degradation processes.